Diseases and Pests Associated to Tomato Cultivation in the Locality of Daloa (Côte d’Ivoire) - Tonessia, Charlotte Dolou; Soumahin, Francis Eric; Denise, Boye Mambé Auguste; Toussaint, Niangoran Yate Atse; Marc, Djabla Jean; Yatty Ju, Zoh Olivia Dominique et Kouadio (JOURNAL OF ADVANCES IN AGRICULTURE, 2018)
This study aims at identifying the major tomato pests and diseases in the locality of Daloa. To achieve this goal, surveys were conducted among tomato farmers in the city, the outskirts and the villages of Daloa. They consisted in questioning farmers about their identity, the cropping practices and the problems encountered in the practice of tomato cultivation. Then another step consisted in monitoring tomato farms for observing diseases and pests associated to tomato. The results of the study showed that tomato cultivation is concentrated in rural areas and is carried out by men with a very low level of education. The most cultivated varieties are petromech and cobra because of their resistance to certain pests. Several tomato diseases have been identified, however the most significant were seedling damping-off (Pythium sp, Fusarium sp, Rhizoctonia solani), plant wilting (Fusarium oxyporum and Ralstonia solanacerum), fruit anthracnose (Colletotrichum sp.), apical necrosis and root-knot nematode (Meloidogyne sp.). The main pests observed on tomato in the locality were Helicoverpa armigera (Lepidoptera), Bemisia tabaci (Homoptera), Dysdercus sp. (Hemiptera). This study provides a pathway from which further studies including mapping the different diseases could be conducted so as to better monitor and protect tomato cultivation.